THE FIRST DATA ON HYDROGEN AND OXYGEN ISOTOPIC COMPOSITIONS IN THE THERMAL MINERAL WATERS OF EASTERN CHUKOTKA - Cheshko A.L.; Lavrushin V.Yu.; Polyak B.G.; Dubinina E.O.; Vakin E.A. (My University, 2004)
The chloride-sodium hydrothermal waters (TDS content up to 36 g/l) that discharge into the coastal regions of Chukotka are traditionally attributed to unaltered or differently metamorphosed seawaters Hydrothermal waters with similar salt and gas compositions are known in the coastal regions of the Russian Far East, as well as in Japan, Iceland, and other countries. Kononov and Tkachenko identified them as specific coastal or marine hydrothermal waters. Such view on the genesis of hydrothermal waters in Chukotka is not supported by hydrogen and oxygen isotope data. However, it should be emphasized that it is only these data, rather than other hydrochemical characteristics, that can unambiguously solve the problem of water origin, since the main types of natural waters (meteoric, marine, and juvenile) are characterized by specific values of δD and δD18O. Therefore, in July-August, 2002, we sampled the thermal mineral waters of eastern Chukotka, as well as marine and local surface waters. The study of hydrothermal waters in Chukotka was also motivated by a desire to refine thermal energy resources there, because their utilization in this cold region, with its harsh climate and permafrost, is an especially important issue.